Clinical pathway for laparoscopic cholecystectomy - Perez-Guarinos, Carmen V.; Baeza-Murcia, Melody; Liron-Ruiz, Ramon J.; Aguayo-Albasini, Jose L. (International Surgery Journal, 2016)
We write this letter regarding the article retrospective analysis of clinical pathway in management of laparoscopic cholecystectomy in a tertiary care centre in South India, article we have read with interest, and because of the citation of our centre’s article clinical pathway for laparoscopic cholecystectomy.